IMPROVING THE QUALITY OF PERFORMANCE MONITORING OF THE WORK UNITS OF THE NATIONAL LAND AGENCY OF ACEH PROVINCE - Rendy Fahmi Roza; Dedi Purwanto; Nova Mayasari (INFOKUM, 2022)
This study describes a system that functions to monitor performance achievements, where technological developments in the millennial era are very rapid so that they are able to have a large enough effect, especially in the world of work. Achievement of performance in an organization is very important so that the work of an organization can be achieved according to the target. At the Ministry of ATR/BPN, many dashboards have been made that can monitor this performance achievement, but due to too many dashboards spread over many applications, it is difficult for the supervisory officers of the Aceh Province BPN Regional Office to monitor and evaluate, it is necessary to have a system that can collect all achievements. performance byrealtimeand fast, so that with a system that is integrated into all dashboards, it will make it easier for supervisory officials to monitor and evaluate all activities anytime and anywhere.